2012
DOI: 10.1074/jbc.m112.417832
|View full text |Cite
|
Sign up to set email alerts
|

Isocitrate Dehydrogenase (IDH) Mutations Promote a Reversible ZEB1/MicroRNA (miR)-200-dependent Epithelial-Mesenchymal Transition (EMT)

Abstract: Background: Isocitrate dehydrogenase (IDH) mutations occur in diverse tumor types, leading to production of the oncometabolite 2-hydroxyglutarate (2-HG). Results: High 2-HG levels lead to a reversible epithelial-mesenchymal transition (EMT) phenotype, which is dependent on ZEB1/miR-200. Conclusion: Mutant IDH reversibly disrupts normal epithelial morphology through EMT induction, a possible tumorigenic mechanism. Significance: This is the first report of a reversible mutant IDH-dependent signaling phenotype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
85
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(97 citation statements)
references
References 67 publications
(80 reference statements)
7
85
0
1
Order By: Relevance
“…However, across multiple expression conditions and cell types, IDH2 Arg-140 mutations consistently result in less 2HG accumulation than IDH2 Arg-172 mutations. A recent report doc- umenting similar differences when these mutations were knocked-in to an endogenous IDH2 allele in colon cancer cells via homologous recombination provides further support for this finding (30). Here, we demonstrate that the quantitative difference in 2HG accumulation between IDH2 Arg-140 and Arg-172 mutations is within a range that can variably alter gene expression in non-transformed cells and the ability of these lineage-specific progenitor cells to differentiate into terminally differentiated cells.…”
Section: Discussionsupporting
confidence: 59%
“…However, across multiple expression conditions and cell types, IDH2 Arg-140 mutations consistently result in less 2HG accumulation than IDH2 Arg-172 mutations. A recent report doc- umenting similar differences when these mutations were knocked-in to an endogenous IDH2 allele in colon cancer cells via homologous recombination provides further support for this finding (30). Here, we demonstrate that the quantitative difference in 2HG accumulation between IDH2 Arg-140 and Arg-172 mutations is within a range that can variably alter gene expression in non-transformed cells and the ability of these lineage-specific progenitor cells to differentiate into terminally differentiated cells.…”
Section: Discussionsupporting
confidence: 59%
“…SOX9 is an embryonic transcription factor and key regulator of the mammary stem cell Figure 18). H3K4me3 was globally increased in promoter regions of genes regulating EMT, axon guidance, and stemness ( Figure 10, A-C), in cells with IDH mutations (37,38). We also show that D-2HG by itself induces these phenotypes.…”
Section: D-2hg Is the Predominant Enantiomer Elevated In Human Breastmentioning
confidence: 59%
“…A key finding of our study is the discovery that both ADHFE1 and D-2HG similarly induce EMT, stemness, and invasion of mammary cells. It has previously been shown that mutant IDH and D-2HG promote EMT in human colon cancer cells (30,37). Similarly, accumulation of fumarate in fumarate hydratase-deficient cells induces EMT through inhibition of a Tet-mediated demethylation process in the regulatory region of the miR-200ba429 cluster (51).…”
Section: Discussionmentioning
confidence: 99%
“…These metabo lites are able to in hibit α ke tog lu tarate de pen dent dioxy ge nases among which the afore men tioned HIF 1α neg a tive reg u la tor PHD2 [214][215][216], but also TET fam ily of 5 methyl cy to sine hy drox y lases and Ju monji fam ily of hi s tone demethy lases [217][218][219], as pre vi ously dis cussed in para graph 2. In hi bi tion of the last two re sults in DNA and hi s tone hy per me thy la tion which, in turn, re presses miR 200 ex pres sion [220,221] and/ or in duces EMT re lated tran scrip tion fac tors [220], lead ing to re pres sion of ep ithe lial mark ers, ex pres sion of mes enchy mal mark ers, and ac qui si tion of mi gra tory and in va sive traits [213,220,222,223].…”
Section: Metabolic Contribution To Cancer Metastasismentioning
confidence: 99%